Towards a Sustainable Future: Developing a Framework for Social Business Performance in the Context of Environmental Orientation and Government Support - Sandy Francis, Peris; Prasun, Das Gupta; Abdur, Rahaman; Isbat, Uddin; Farhana Haque, Purnima; Khan Sarfaraz, Ali; Ida, Hindarsah (INTI International University, 2025)
In recent years, there has been a significant increase in the attention of academia and industry on different social issues, sustainability, and green practices. Most importantly, both government and private sectors are becoming more concerned to create a sustainable business environment that will not only focus on profit but also act responsibly for the development of society and the environment. And the situation is almost the same in the developed, developing, and underdeveloped countries. As business plays a great role in our everyday life, this paper focuses on the development of Social Business Performance. And to do that, government support is considered in this paper as one of the key sources to influence the social business and the private sector’s environmental concern. This study also included the environmental orientation to see the influences on the relations. This paper's primary goal may be divided into two groups. One provides a conceptual framework for this field of study, while the other is a guideline for potential future studies. Insights and recommendations from earlier studies are presented in this report for the government, business firms, policy makers, and stakeholders. The important overviews and reviews on this topic are also included in the study. Additionally, as the number of studies on social business and other relevant issues is limited, this paper argues that researchers should focus on the development of social business performance.